Socio-Economic Conditions in Community Welfare in the Border Area of "‹"‹Sajingan Besar District, Sambas Regency - Wardani, Sandra Fitria; Mandala, Yoga; Gustriansyah, Edy (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study aims to comprehensively examine the socio-economic conditions and overall welfare of communities in the border region of Kecamatan Sajingan Besar, Sambas Regency. The research addresses the gap in literature concerning the multidimensional aspects of welfare in border areas, where economic opportunities are interlaced with vulnerabilities. Employing a qualitative case study design, data were collected through purposive sampling and semi-structured interviews with local residents, community leaders, village officials, and economic actors. Analysis of the data reveals that the majority of the population possesses only basic education, significantly limiting access to competitive job opportunities and perpetuating economic instability. With 66.4% of residents engaged in agriculture, the local economy is highly dependent on seasonal outputs and lacks diversification, resulting in fluctuating incomes and vulnerability to external shocks. Although community-based health services such as Posyandu play a crucial role in providing essential care, the overall access to quality healthcare remains inadequate. Additionally, low levels of social participation and limited access to information further hinder community development. The discussion emphasizes that these interrelated factors"”educational deficits, economic dependence on agriculture, insufficient healthcare, and weak social cohesion"”contribute to sustained low welfare levels. The study concludes by recommending integrated, context-specific policy interventions aimed at improving educational access, diversifying economic activities, enhancing healthcare services, and fostering stronger community engagement to promote sustainable development in this border region.